Development Analysis of Signal Pedestrian Crossing Capabilities with Arduino Platform - Yustim, Benny (International Journal of Psychosocial Rehabilitation, 2020)
Growth in population and number of vehicles in big cities results in an increased risk of accidents for road users, especially pedestrians. Based on the Bandung City government report [1], pedestrians are ranked 2nd (two) with the highest risk of death on the highway after 2 (two) motorbike riders, which is 23% of the total number of highway user deaths. The high number of pedestrian deaths is caused by the presence of some motorists who violate vehicle speed limits and ignore pedestrian rights. Technology integration in supporting pedestrian safety, especially when crossing the road is still lacking. Observations in two different places in the center of the city of Bandung, it appears that the new technology is only used to provide a button facility for pedestrians to cross in a very short time scale. The current facility cannot take into account the condition of road waders and vehicle users as well as the weather that occurred at that time. To anticipate the problems, technology integration is more accurate in calculating various conditions around the highway where pedestrians will cross.